Hot excitons increase the donor/acceptor charge transfer yield - Schulze, Michael; Hänsel, Marc; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2014)
Understanding the photoinduced ultrafast charge transfer (CT) dynamics across the donor/acceptor interface is a prerequisite for optimizing the performance of organic photovoltaic devices. Time-resolved second harmonic generation, an interface-sensitive probe with femtosecond temporal resolution, is applied to investigate the well-defined single heterojunction C60/P3HT. The de-excitation of hot singlet excitons in the conduction bands of the polymer into localized excitonic states is observed. In the presence of the electron acceptor, the ultrafast population of a CT state is identified as the dominating relaxation channel. Interestingly, the charge transfer yield correlates with the excitation wavelength and rises with increasing excess energy.